2018
DOI: 10.1159/000486711
|View full text |Cite
|
Sign up to set email alerts
|

Lower Cognitive Function in Older Patients with Lower Muscle Strength and Muscle Mass

Abstract: Background: Low muscle strength and muscle mass are associated with adverse outcomes in older hospitalized patients. The aim of this study was to assess the association between cognitive functioning and muscle strength and muscle mass in hospitalized older patients. Methods: This prospective inception cohort included 378 patients aged 70 years or older. At admission patients were assessed for cognitive functioning by use of the Six-Item Cognitive Impairment Test (6-CIT). Muscle strength and muscle mass were as… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
18
0
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 32 publications
(24 citation statements)
references
References 34 publications
5
18
0
1
Order By: Relevance
“…All cognitive and physical function indicators measured in this study are related and show a decline in aging [83][84][85][86][87][88][89][90][91]. There are strong correlations between tongue pressure and MMSE scores [20,45], and between pulmonary function and MMSE scores [44,46].…”
Section: Discussionmentioning
confidence: 63%
“…All cognitive and physical function indicators measured in this study are related and show a decline in aging [83][84][85][86][87][88][89][90][91]. There are strong correlations between tongue pressure and MMSE scores [20,45], and between pulmonary function and MMSE scores [44,46].…”
Section: Discussionmentioning
confidence: 63%
“…This link is further reinforced by the findings that higher leg power [84] and higher whole-body muscle strength [85] are associated with higher scores in standardized cognitive test batteries. Furthermore, higher handgrip strength is linked to higher scores in general cognitive abilities (e.g., operationalized by MMSE) [86,87] and to higher scores in standardized cognitive test batteries [88][89][90]. Moreover, it was observed that gains in dynamic muscular strength (assessed by one repetition maximum in different resistance exercises) after 6 months of progressive resistance training mediate improvements in global cognitive performance (according to the Alzheimer's Disease Assessment Scale-cognitive subscale) [91].…”
Section: Aging Muscular System and Cognitionmentioning
confidence: 99%
“…The exclusion criteria were the following: (1) patients with depression under pharmaceutical treatment; (2) patients with pathological conditions incompatible with physical exercise; (3) cardiovascular disease, hypopituitarism and malnutrition; (4) illiterate patients; (5) smokers; (6) lived for less than 10 months per year in the current place of residence; (7) attended less than 80% of the sessions of the training programme; (8) showed severe pathologies during the study period; and (9) incomplete measurements. The exclusion criteria were the following: (1) patients with depression under pharmaceutical treatment; (2) patients with pathological conditions incompatible with physical exercise; (3) cardiovascular disease, hypopituitarism and malnutrition; (4) illiterate patients; (5) smokers; (6) lived for less than 10 months per year in the current place of residence; (7) attended less than 80% of the sessions of the training programme; (8) showed severe pathologies during the study period; and (9) incomplete measurements. The study was approved by the Ethics Committee of University of Chile, Santiago de Chile.…”
Section: Samplementioning
confidence: 99%
“…The loss of muscular power is a dominant physical determinant in the loss of functional capacity, especially when the lower limbs are affected. However, the impact of muscular strength training on cognitive function and brain structure is still under debate [7] Furthermore, lower cognitive function has been related to lower muscular strength in older adults [8], and it has been reported that leg strength can help to predict both healthy cognitive ageing and the preservation of brain volume regardless of the genetic factors, life style and vascular risk [9]. Likewise, functional aptitude has been associated with cognitive impairment in older adults, adjusted for sociodemographic factors, chronic disease, health state, health habits and functional state [10].…”
Section: Introductionmentioning
confidence: 99%